A review of vulnerabilities of water systems-related risks in internally displaced persons (IDPs) host communities in Adamawa State, Nigeria - Okem, Andrew; Osei-Amponsah, Charity; Onyeneke, R.; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
This report offers an analysis of the challenges faced by Internally Displaced Persons (IDPs) in Adamawa State, Nigeria, set against the global context of internal displacement. It explores the primary drivers of displacement in the region, including conflict, particularly insurgency activities, and natural disasters like flooding. These factors have led to significant challenges for IDPs, such as safety, shelter, loss of livelihoods, and social disintegration.